Orthosis Management in Patients after Poliomyelitis Anterior Acuta - Bocker, B.; Hoelig, C.; Smolenski, U. C. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2013)
The effect of an orthosis supply in patients with paresis caused by poliomyelitis was to be proved. The main questions was if an orthosis supply might improve the bodily functionality in daily life and especially the muscle activity of the lower limbs and trunk.nonrandomized before-after trial with 3 months follow up.institutional practice, ambulatory care.In a consecutive sample of 13 patients (average age: 63.8 years, 9 female, 4 male) with partial paralysis of the quadriceps muscle and weakness of the dorsal flexors of the foot and instability of the knee joint caused by poliomyelitis anterior acuta 40 years before a femoral orthosis supply was indicated.10 of them fulfilled the inclusion criteria for the study (average age: 64.5 years, 7 female, 3 male).The activity of 8 specified leg and trunk muscles (m.) had to be described 3 months before (baseline=t0), immediately at orthosis supply (t1) and after further 3 months of gait training with the orthosis (t2).The muscle activity was described by the surface- electromyography (s-EMG). By means of the kinematic gait analysis via 3-dimensional ultrasound analysis of movement the knee joint angle and the stance duration of every single leg was detected at the same times.The quality of life was measured by means of 36 Items Short Form Health Survey (SF 36).The significance of all evaluated parameters was detected by the Friedman test (level of significance p</=0.05).Because of 4 dropouts after a 3 months baseline 6 patients (5 female, 1 male, average age: 61 years) were evaluated with an orthosis over a period of 6 months until follow up. On the side without the orthosis, increased s-EMG values of m. obliquus abdominus internus and m. multifideus during standing and of the m. gluteus medius during walking were observed. On the side with the orthosis support changes of both abdominal muscles, rised activity of the vastus medialis and relaxation of m. gluteus medius and m. bizeps femoris during standing were detected, but during walking both abdominal muscles as well as m. multifideus, mm.rectus and bizeps femoris showed higher s-EMG-level whereas both vasti, and m. gluteus medius had decreased values.The knee joint angles showed an increase in the leg with the orthosis of 13° without any hyperextension but a rising in the duration of the stance phase was seen in the leg with the orthosis. The patients quality of life did not change significantly during the observation time.The instable knee could be stabilized by means of an adequate orthosis. Orthotic support of the paretic limb can relieve the overstrained muscles but a sufficient activity of the m. gluteus medius at the stable leg and of the abdominal muscles and in all probability of m. multifideus on both sides is necessary to indicate orthosis supply.
Keywords: poliomyelitis anterior acuta; paresis; orthosis; gait parameter